Bio-based aliphatic primary amines from alcohols through the 'Nitrile route' towards non-isocyanate polyurethanes. (September 2016) - Hibert, Geoffrey; Lamarzelle, Océane; Maisonneuve, Lise; Grau, Etienne; Cramail, Henri
Graphical abstract: Highlights: Nitrile compounds were prepared under mild aerobic oxidation from primary aliphatic bio-based alcohols. A series of bio-based aliphatic primary amines were prepared by reduction of the corresponding nitrile compounds. Fully bio-based NIPUs from di-amines and biscarbonates were prepared. Abstract: Bio-based primary amines obtained from the corresponding alcohols via nitrile intermediates and their subsequent polymerizations with cyclic carbonates are described. Nitrile compounds were synthesized under mild aerobic oxidation of primary aliphatic alcohols. CuI, bipyridine and TEMPO were used as a catalytic system, in the presence of aqueous ammonia and O2 . A series of bio-sourced alcohols were successfully oxidized into nitriles using this catalytic system. The so-formed bio-based dinitriles were subsequently reduced into primary diamines under H2 in the presence of Ni Raney. The latter were polymerized with fatty acid-based bis-cyclic carbonates for the design of fully bio-based poly(hydroxyurethane)s.